Wearable Ankle Robots in Post-stroke Rehabilitation of Gait: A Systematic Review - Shi, Bin; Chen, Xiaofeng; Yue, Zan; Yin, Shuai; Weng, Qipeng; Zhang, Xue; Wang, Jing; Wen, Weina (Frontiers in Neurorobotics, 2019)
Background: Stroke causes the weak functional mobility of survivors and affects their ability to perform activities of daily living. Wearable ankle robots are a potential intervention for gait rehabilitation post-stroke. Objective: The aim of this study is to provide a systematic review of wearable ankle robots, focusing on the overview, classification and comparison of actuators, gait event detection, control strategies and performance evaluation. Method: Only English-language studies published from December 1995 to March 2019 were searched in the following databases: PubMed, EMBASE, Web of Science, Scopus, IEEE Xplore, Science Direct, SAGE journals. Result: A total of forty-eight articles were selected and 97 stroke survivors participated in these trials. Findings showed that few comparative trials were conducted among different actuators or control strategies. Moreover, mixed sensing technology which combines kinematic with kinetic information was effective to detect motion intention of stroke survivors. Besides, all the selected clinical studies showed improvement in peak dorsiflexion degree in swing phase, peak paretic propulsive during push-off and further enhance walking speed after a period of robot-assisted ankle rehabilitation training. Conclusions: Preliminary findings suggest that wearable ankle robots have certain clinical benefits for the treatment of hemiplegic gait post-stroke. Efforts should be invested in performing a larger multicenter randomized controlled clinical trial to enhance the clinic effectiveness of wearable ankle robot in the future research.